Mechanism based diffusion-reaction modelling for predicting the influence of SARA composition and ageing stage on spurt completion time and diffusivity in bitumen. (18th January 2021) - Mühlich, Uwe; Pipintakos, Georgios; Tsakalidis, Christos
Highlights: Continuum thermodynamics provides a frame for modeling oxidative ageing in bitumen. The examined model accounts for the dependence of oxidative ageing on composition. Mechanisms at molecular level are linked to the continuum scale by activity models. Abstract: Diffusion-reaction models derived within the frame of continuum thermodynamics of irreversible processes for reacting mixtures enjoy a number of advantages over purely phenomenological models. This paper explores the potential and challenges of this approach by means of a particular model for spurt oxidation in bitumen. Film ageing experiments are simulated considering different bitumen compositions in terms of SARA fractions. The predicted spurt completion times are contrasted with parameters characterizing the initial composition. The results demonstrate the consistency of the model. Furthermore, the trend regarding spurt completion time predicted by the model is in line with experimental results from the Strategic Highway Research Program (SHRP). In addition, the change in diffusivity due to oxidation is discussed for different compositions. The model consistently predicts a significant decrease in diffusivity due to oxidation in the absence of out-diffusion of reaction products.